MicroRNAs in Huntington’s Disease: Diagnostic Biomarkers or Therapeutic Agents? - Dong, Xiaoyu; Cong, Shuyan (Frontiers in Cellular Neuroscience, 2021)
MicroRNA (miRNA) is a non-coding single-strand small molecule of about 21 nucleotides. It degrades or inhibits the translation of RNA by targeting the 3’ UTR. miRNA plays an important role in the growth, development, differentiation, and functional execution of the nervous system. Dysregulated miRNA expression has been associated with several pathological processes of neurodegenerative disorders, including Huntington’s disease (HD). Recent studies also suggested promising roles for miRNAs as biomarkers and potential therapeutic strategies for HD. Here, we review the emerging role of dysregulated miRNAs in HD and describe general miRNA biology, their pathophysiological implications, and their potential roles as biomarkers and therapeutic agents.